Endocrine mucin-producing sweat gland carcinoma: a systematic review and meta-analysis. (19th May 2022) - Froehlich, Michael H.; Conti, Keith R.; Norris, Ivy I.; Allensworth, Jordan J.; Ufkes, Nicole A.; Nguyen, Shaun A.; Bruner, Evelyn T.; Cook, Joel; Day, Terry A.
Abstract: Background: Endocrine mucin-producing sweat gland carcinoma is a rare, under-reported cutaneous adnexal tumor that is often misdiagnosed and has an unknown incidence of metastasis. Objective: To determine the incidence of metastasis and tumor recurrence, as well as diagnostic accuracy and current trends in treatment modality. Methods: A search was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Tumor pathology and clinical data concerning demographics, presentation, diagnosis, treatment and follow-up were assessed. Results: A total of 36 publications with 110 cases were identified. Initial pathological diagnosis was incorrect in 45.5% of cases. One case of metastatic disease was reported. The incidence of locoregional recurrence was 10.6% over a mean follow-up period of 21.3 months. Of cases with known methods of resection, 34.6% were resected by excisional biopsy, 42.8% were resected by wide surgical excision, and 31.3% were cleared by Mohs micrographic surgery. Limitations: The low reported incidence and level of evidence was suboptimal with only case reports and retrospective case studies being reported. Conclusion: Reported cases of this pathology demonstrate poor diagnostic accuracy. High rates of misdiagnosis and inadequate definitive treatment suggest the need for more comprehensive work-up and management of lesions suspicious for this pathology.